Mobile Creches: Innovating for Inclusive and Quality Early Childhood Development Programs. Issue 6 (2nd November 2021) - Jain, Amrita; Singh, Deepshikha
Abstract : The benefits of early childhood education are well known, but access to quality programs is a challenge for children living in marginalized communities.